(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to evaluate the factors that affect the behavior of students with Down syndrome (DS) in a gamified learning system environment of a SPED school in Baguio City, Philippines. Education focused on the area that uses unique instructional methods, materials, learning aids, and toolkits to meet the educational needs of students with learning incapacities. This study investigated the extent to which a sample of special education teachers addressed several interesting issues with students who have learning infirmities, behavior disorders, and performance concerns. A survey instrument was employed to gather information about topical issues that involve complex subjects typically not addressed in the traditional academic curriculum in school. DS is the most common genetic cause of intellectual disability worldwide, with language being one of the most affected areas. The author hypothesizes factors that contribute to engagement with a learning activity and provides an example of the use of these factors in practice. The authors deeply study a number of the literature regarding gamification and engagement of learners previous to the look of the model, conduct many interviews, and incorporate all information gathered before the design of the framework. However, theories of learning and engagement, particularly in the sphere of higher education, typically fail to consider gaming engagement theory before behaviorism.